Strategi Pemasaran Jagung Di Sentral Produksi Jagung Di Propinsi Sumatera Barat - Ariusni Ariusni (Universitas Negeri Padang, 2018)
This study aims to analyze the identification of internal and external Potential faced in corn marketing by corn farmers in corn central of West Sumatra Province. The research method used Determination of population and sample. The population in this study were corn farmers who numbered as many as 468 people. Sampling is done randomly. 3) Data Collection Method consists of: Secondary data obtained from the Office of Food Agriculture at Provincial Level, Industry and Trade Office, Bappeda West Sumatra Province, Chamber of Commerce, BPS, Financial Institutions, State Institutions, and Provincial Economy. Primary data were collected by using questionnaire. The analytical method of analyzing the potential and problems faced by corn farmers is used SWOT analysis. The results of the study found that the main strengths in corn development were the minimum pricing of maize by the government and 8 opportunities and 6 threats encountered in the development of maize. There are 4 strategies that can be done in the development of corn market of farmers in central corn.